ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI LIMIT FUNGSI ALJABAR - Kulsum, Sri Islami (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
In accordance with the problem limitation, the objective in this study is to find out the percentage of errors made by students in solving mathematical problems in the algebraic function limit material. Descriptive research with a qualitative type approach used in this study. One high school in West Bandung regency, Darul Falah High School, is the subject of this study. A diagnostic test was given in the form of a matter description of the algebraic function limit to 21 students as a sample. The object to be reviewed is an error made by the student in solving the problem. The type of error is taken from the classification written by Herman Hudoyo, namely there are concept errors, procedural errors, and operating errors. From the results obtained, the percentage of student errors in completing mathematical problems material limits on algebraic functions in the concept type by 34.5% is categorized high enough for the type of procedure to get 36.9% categorized quite high while the type of operation by 61.9% is categorized very low. This indicates, students still have difficulty in operating a number, especially in numbers with positive and negative signs. Inaccurate and lack of understanding of students is the cause of errors that arise so that there is a need for follow-up to overcome these errors so that similar errors do not occur.